Hypolimnetic oxygenation 2: oxygen dynamics in a large reservoir with submerged down-flow contact oxygenation (Speece cone). (3rd July 2019) - Horne, Alex J.; Jung, Rodney; Lai, Hubert; Faisst, Bill; Beutel, Marc
Abstract: Horne AJ, Jung R, Lai H, Faisst B, Beutel, M. 2019. Hypolimnetic oxygenation 2: oxygen dynamics in a large reservoir with submerged down-flow contact oxygenation (Speece cone). Lake Reserv Manage. 35:323–337. Low dissolved oxygen (DO) in the sediments of Camanche Reservoir, California (513 million m 3, 31 km 2 ), produced toxic hydrogen sulfide (H2 S). Direct hypolimnetic oxygenation suppressed H2 S without provoking early destratification and cold-water fish problems downstream. A cool, bubble-free plume directed horizontally over the sediments was chosen over a rising bubble plume. A submerged, down-flow contact oxygenator (Speece cone) pumped anoxic water from 5 m above the sediments to the top of a 7 m high cone to dissolve a counterflow of rising pure oxygen bubbles. The bubble-free, highly oxygenated discharge (80 mg/L) was diluted to fish-safe levels (8 mg/L) and directed up-reservoir via jets in a 45 m long manifold. Placing the cone on the bottom near the dam increased hydraulic pressure and doubled oxygen solubility. Poor-quality hypolimnion water (DO <2 mg/L, redox 18–100 mV, H2 S odors) was converted to good-quality water (DO 3–7 mg/L, redox >300 mV, no H2 S odors). Comparing preoxygenation hypolimnion DO decline (0.1 mg/L/d) with oxygenation temporarily switched off (0.23 mg/L/d) gave a full-scale estimate of induced hypolimnion oxygen demand. In 1994, the oxygenated plume moved 4.5 km upstream at 0.1 cm/s via natural water motion. No long pipes were needed. About 18% of the bottom hypolimnion was directly oxidized in the cone and 1.8 times the total volume was indirectly oxidized via entrainment in the plume. After 10 yr, oxygen additions were reduced by >50% with no deleterious effects.